2014
DOI: 10.1186/1479-5876-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate miRNA biomarkers from miRNA regulatory network with application to prostate cancer

Abstract: BackgroundMicroRNAs (miRNAs) are a class of non-coding regulatory RNAs approximately 22 nucleotides in length that play a role in a wide range of biological processes. Abnormal miRNA function has been implicated in various human cancers including prostate cancer (PCa). Altered miRNA expression may serve as a biomarker for cancer diagnosis and treatment. However, limited data are available on the role of cancer-specific miRNAs. Integrative computational bioinformatics approaches are effective for the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 55 publications
(69 reference statements)
2
108
0
Order By: Relevance
“…In this work, we employed POMA to identify key miRNAs expressed in samples obtained from ITP patients that were newly diagnosed (G1) versus managing a chronic ITP condition (G2). POMA is a framework that has been used to identify candidate miRNA biomarkers for diseases by integrating microarray profiling with experimental and predicted miRNA-mRNA interactions [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we employed POMA to identify key miRNAs expressed in samples obtained from ITP patients that were newly diagnosed (G1) versus managing a chronic ITP condition (G2). POMA is a framework that has been used to identify candidate miRNA biomarkers for diseases by integrating microarray profiling with experimental and predicted miRNA-mRNA interactions [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed miRNAs and/or genes were then mapped to the whole network to infer specific miRNA-mRNA subnetworks [12, 20]. According to the framework, stage-specific miRNA-mRNA networks were built, and key miRNAs in the subnetworks were identified on the basis of significant differential expression of miRNAs and genes between each ITP group and the N group using improved POMA [29, 30]. We also constructed a G2’ miRNA–mRNA network based on the identification of DE-miRNAs and DE-mRNAs between G2 and G1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Zhang et al [81] identified 39 novel miRNAs candidates as PCa biomarkers analyzing Gene Expression Omnibus datasets for PCa and benign prostatic hyperplasia (BPH) using bioinformatics tools, considering the regulatory power of miRNAs. Results were verified by qRT-PCR concluding that miRNA-648 could be a novel biomarker of PCa.…”
Section: Functional Enrichment Resources For Mirna Analysismentioning
confidence: 99%
“…We found that approximately 1.3% of the predicted miRNA targets formed reciprocal "up-down" or "down-up" expression relationships with miRNAs, suggesting that the modulation of miRNA-mRNA interactions could be promising biomarkers for cancers. Integrated expression analysis of miRNAs and mRNAs using microarray technology have revealed signatures implicated in ovarian cancer [165,166] , breast cancer [167][168][169][170][171] , metastatic osteosarcoma [172] , gastric cancer [173,174] , pancreatic cancer [175] , oral squamous cell carcinoma [176] , lung cancer [177][178][179] , prostate cancer [180,181] , follicular thyroid tumors [182] , retinoblastoma [183] , etc. The miRNA/mRNA interactome not only includes the interactions between an miRNA and its targets but also comprises the TF-miRNA network.…”
Section: Integrated Analysis Of Mirnas and Mrnas In Cancermentioning
confidence: 99%